Dlaczego warto uczyć interpretacji? - Jaskóła, Ewa (Postscriptum Polonistyczne, 2020)
The article presents the possibilities of using the techniques of synestics in the process of teaching how to interpret poetry. The author of the article uses exercises and techniques of synestics in two functions: educational and didactic. She creates situation in which students have not read the text they were asked to read and explains how exercises can lead to developing selfawareness that encourages reading. A lesson that leads to interpreting Anna Świrszczyńska’s poem Budowałam barykadę [I Built a Barricade] motivates reading Adam Mickiewicz’s Reduta Ordona [Ordon’s Redoubt]. The author describes a process of presenting poetic texts to the lower secondary school student in a way that makes him realize important existential problems undertaken by the poetry.